2017
DOI: 10.12973/eurasia.2017.00683a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Career Motivation on Science Learning in Korean High-School Students

Abstract: Motivation to learn is an essential element in science learning. In this study, the role of career motivation in science learning was examined. In particular, first, a science motivation model that focused on career motivation was tested. Second, the role of career motivation as a predictor of STEM track choice was examined. Third, the effect of gender and academic year on science motivation was explored. The participants of the study were 626 highschool students. We used the Rasch analysis, structural equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 57 publications
3
32
0
6
Order By: Relevance
“…There was a big gender gap in the level of STEM career motivation in Korea in this study. This finding is consistent with the results of previous studies showing that Korean female students do not aspire or intend to have a science career as much as male students do (Shin et al, 2017). At the same time, Korean female high-school students showed much less overall STEM career motivation than middle-school students.…”
Section: Association Between Constructs Of Stem Career Motivationsupporting
confidence: 91%
See 2 more Smart Citations
“…There was a big gender gap in the level of STEM career motivation in Korea in this study. This finding is consistent with the results of previous studies showing that Korean female students do not aspire or intend to have a science career as much as male students do (Shin et al, 2017). At the same time, Korean female high-school students showed much less overall STEM career motivation than middle-school students.…”
Section: Association Between Constructs Of Stem Career Motivationsupporting
confidence: 91%
“…This paradoxical phenomenon has so far been studied mainly in terms of cultural context, such as Confucianism and collectivism, which are common value systems in East Asia. One reason for such a paradoxical situation is that a Confucian culture highly emphasizes the role of education in society; parents have a passion for their children's education in collectivist cultures (Lee, Rojewski, & Hill, 2013;Shin, Ha, & Lee, 2017). In addition, a ''big fish little pond effect'' model, in which students who have shown high average achievement tend to have a low self-concept because of social comparison or pressure, has been suggested as a plausible reason for East Asian students' low self-concept for math and science (Liou, 2014;Marsh et al, 2008).…”
Section: Korean Socio-cultural Background Related To Stem Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…By noticing relevance, students might be more encouraged to participate and as a result, profit from the lessons with the added bonus of language acquisition. Shin, Lee and Ha (2017) examined the influence of career motivation on science learning and found that it has a direct influence on several motivational factors such as self-determination and self-efficacy. Another personal impact factor is described by participant 2.…”
Section: Discussionmentioning
confidence: 99%
“…The principles of cooperative learning that are applied in small groups (Bellanca et al, 2010;Slavin, 2014), provide more space for students to take on the role and work together as a learner (Cetindamar & Hopkins, 2008;Jasti et al, 2014). Social interactions that occur in learning activities affect how students master the material (Pang, Lau, Seah, Cheong, & Low, 2018;Shin, Lee, & Ha, 2017). Some researchers believe that cooperative attitudes can grow with a pattern of habituation in the learning process (Scott, 2015;Triyanto, 2018).…”
Section: Figure 2 Cooperative Of Student Skills On Embryology Coursementioning
confidence: 99%